Training to Enhance the Knowledge and Comfort Level of Emergency Physicians Providing Care for Survivors of Sexual Assault. Issue 1 (6th July 2023) - Prusky, Melissa A.; Solomon, Chloe J. E.; Tracy, Kaitlynn P.; Shah, Shital C.; Rodriguez, Jaclyn; Balata, Maria; York, Sloane L.; Rumoro, Dino P.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: Although sexual assault (SA) is a substantial public health problem, emergency physicians do not universally undergo continuing education on caring for survivors of SA. The goal of this intervention was to develop a training course that improves physician understanding of trauma-sensitive care in the emergency department and equips physicians with knowledge of the specialized care required to treat SA survivors. Methods: Thirty-nine attending emergency physicians underwent a 4-hour training on trauma-sensitive care for survivors of SA and completed prequestionnaires and postquestionnaires to assess training efficacy in improving knowledge base and comfort level providing care. The training consisted of didactic portions focused on the neurobiology of trauma, communication skills, and forensic evidence collection techniques and a simulation portion with standardized patients to practice evidence collection and a trauma-sensitive anogenital examination. Results: Physicians demonstrated significantly improved performance ( P < .05) on 12 of 18 knowledge-based questions. Physicians also showed significant improvement ( P < .001) on 11 of 11 Likert scale questions that assessed comfort level communicating with survivors and using trauma-sensitive techniques during medical and forensic examinations. Conclusion: Physicians who received the training course demonstrated a significantly improved knowledge base and comfort level treating survivors of SA. Considering the prevalence of sexual violence, it is imperative that physicians are appropriately educated on trauma-sensitive care.